Compression behaviour of wire+ arc additive manufactured structures - Abbaszadeh, Masoud; Ventzke, Volker; Neto, Leonor; Riekehr, Stefan; Martina, Filomeno; Kashaev, Nikolai; Hönnige, Jan Roman; Williams, Stewart W.; Klusemann, Benjamin (MDPI, 2021)
Increasing demand for producing large-scale metal components via additive manufacturing requires relatively high building rate processes, such as wire + arc additive manufacturing (WAAM). For the industrial implementation of this technology, a throughout understanding of material behaviour is needed. In the present work, structures of Ti-6Al-4V, AA2319 and S355JR steel fabricated by means of WAAM were investigated and compared with respect to their mechanical and microstructural properties, in particular under compression loading. The microstructure of WAAM specimens is assessed by scanning electron microscopy, electron back-scatter diffraction, and optical microscopy. In Ti-6Al-4V, the results show that the presence of the basal and prismatic crystal planes in normal direction lead to an anisotropic behaviour under compression. Although AA2319 shows initially an isotropic plastic behaviour, the directional porosity distribution leads to an anisotropic behaviour at final stages of the compression tests before failure. In S355JR steel, isotropic mechanical behaviour is observed due to the presence of a relatively homogeneous microstructure. Microhardness is related to grain morphology variations, where higher hardness near the inter-layer grain boundaries for Ti-6Al-4V and AA2319 as well as within the refined regions in S355JR steel is observed. In summary, this study analyzes and compares the behaviour of three different materials fabricated by WAAM under compression loading, an important loading condition in mechanical post-processing techniques of WAAM structures, such as rolling. In this regard, the data can also be utilized for future modelling activities in this direction.
Keywords: Ti-6Al-4V; AA2319; compression test; EBSD